World development report 1979. - World Bank; World Bank. (Washington, D.C. The World Bank, 1979)
Structural transformation is particularly important for middle income countries. In dealing with the appropriate policies to be associated with structural changes, this report analyzes the processes of industrialization, urbanization, and the sectoral deployment of labor. The challenges identified, analyzed, and presented for consideration are: (i) creation of job opportunities for an additional half billion people that will join the labor force in the developing countries by 2000; (ii) accommodation of an additional one billion people in the same time perspective in the urban areas of the developing countries in socially acceptable and economically productive conditions; (iii) creation of an international trade environment that is supportive of the development efforts; and (iv) significant steps to the elimination of absolute poverty.
Keywords: Economic assistance; Underdeveloped areas -- Economic conditions; Underdeveloped areas -- Economic indicators